Novel Horizons in Postbiotics: Lactobacillaceae Extracellular Vesicles and Their Applications in Health and Disease - González-Lozano, Elena; García-García, Jorge; Gálvez, Julio; Hidalgo-García, Laura; Rodríguez-Nogales, Alba; Rodríguez-Cabezas, María Elena; Sánchez, Manuel (Nutrients, 2022)
Lactobacillus probiotics contained in dietary supplements or functional foods are well-known for their beneficial properties exerted on host health and diverse pathological situations. Their capacity to improve inflammatory bowel disease (IBD) and regulate the immune system is especially remarkable. Although bacteria–host interactions have been thought to occur directly, the key role that extracellular vesicles (EVs) derived from probiotics play on this point is being unveiled. EVs are lipid bilayer-enclosed particles that carry a wide range of cargo compounds and act in different signalling pathways. Notably, these EVs have been recently proposed as a safe alternative to the utilisation of live bacteria since they can avoid the possible risks that probiotics may entail in vulnerable cases such as immunocompromised patients. Therefore, this review aims to give an updated overview of the existing knowledge about EVs from different Lactobacillus strains, their mechanisms and effects in host health and different pathological conditions. All of the information collected suggests that EVs could be considered as potential tools for the development of future novel therapeutic approaches.